Exploring the Advantages of English Club in Improving Speaking Skill at Columbia Nursing Academy Year 2022/2023 - Madina; Sidabutar, Lita Imanuela (PT FORMOSA CENDEKIA GLOBAL, 2024)
The courage of students in honing their speaking skills to become confident with English club activities such as in this study.